A first course in numerical analysis - Ralston, Anthony (McGraw-Hill Book Company, 1965)
his outstanding text by two well-known authors treats numerical analysis with mathematical rigor, but presents a minimum of theorems and proofs. Oriented toward computer solutions of problems, it stresses error analysis and computational efficiency, and compares different solutions to the same problem.